2015
DOI: 10.3390/environments2010001
|View full text |Cite|
|
Sign up to set email alerts
|

Land Conversion Dynamics in the Borana Rangelands of Southern Ethiopia: An Integrated Assessment Using Remote Sensing Techniques and Field Survey Data

Abstract: Conversion of rangelands into cultivated land is one of the main challenges affecting the management of rangelands in Ethiopia. In order to inform policy makers about trends in land-use conversion, this study examined the drivers, trends, and impacts of land conversions in five locations selected in the Borana rangelands of Southern Ethiopia. This study integrated survey interviews from agro-pastoralists, participatory appraisals, rainfall data, and remotely sensed satellite data from Landsat images taken in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
18
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 30 publications
8
18
2
Order By: Relevance
“…Generally, bare land cover was increased at a rate of 22.3 % annually during the study period ( Table 2). The result of this study is in agreement with the findings of previous studies from arid and semi-arid rangelands (Tegegn et al, 2011;Elias et al, 2015;Yonas et al, 2016), which reported high levels of bare soil in the rangelands.…”
Section: Magnitude Of Lulc Changessupporting
confidence: 83%
See 4 more Smart Citations
“…Generally, bare land cover was increased at a rate of 22.3 % annually during the study period ( Table 2). The result of this study is in agreement with the findings of previous studies from arid and semi-arid rangelands (Tegegn et al, 2011;Elias et al, 2015;Yonas et al, 2016), which reported high levels of bare soil in the rangelands.…”
Section: Magnitude Of Lulc Changessupporting
confidence: 83%
“…On the other hand, the increase in grassland in different rangelands was reported from areas of the country, where the restoration activities by different government and non-governmental organisations (NGOs) were common (Elias et al, 2015). This suggests the importance of restoring degraded rangelands for improving grass cover (Walkaro, 2007;Abate et al, 2010) (Table 2).…”
Section: Magnitude Of Lulc Changesmentioning
confidence: 99%
See 3 more Smart Citations